Analisis Kesulitan Siswa pada Pembahasan Materi Pengelolaan Data Kelas VI SDN Kalideres 06 Pagi - Unaenah, Een; Siregar, Epriliani Rahmita; Nurjamilah, Putri; Ramadhanty, Salwa; Sarah, Sarah (Lembaga Yasin AlSys, 2022)
This study aims to analyze student’s difficulties in discussing the material for data management for class VI. Regarding Mathematics learning related to understanding the material, discussion, student difficulties and the teacher's efforts to overcome the student's difficulties. The research method used is a qualitative research method with data collection in the form of interviews, documentation, and observations. The results of this study reveal how the difficulties in data management are (mean, median, and mode). In grade VI students, it has been seen how many students already understand and which students have difficulty understanding the learning material. Students' difficulties can be influenced by lack of attention in learning (concentration), lack of student response when participating in teaching and learning activities (reaction) and the slow thinking power of students in understanding the material.